1.6.7a Hydraulic circuit with cylinder controlled by a 4/3 DCV, of semi-closed/cnergy regenerative connection - M.Galal Rabie (McGraw-Hill's AccessEngineering., 2024)
Circuit illustrating the semi-open (energy regenerating) operating mode of a hydraulic circuit